Episensitization: Defying Time’s Arrow - Oronsky, Bryan T.; Oronsky, Arnold L.; Lybeck, Michelle; Oronsky, Neil C.; Scicinski, Jan J.; Carter, Corey; Day, Regina M.; Rodriguez Orengo, Jose F.; Rodriguez-Torres, Maribel; Fanger, Gary F.; Reid, Tony R. (Frontiers in Oncology, 2015)
The development of cancer is driven by complex genetic and epigenetic changes that result in aberrant and uncontrolled cellular growth. Epigenetic changes, in particular, are implicated in the silencing or activation of key genes that control cellular growth and apoptosis and contribute to transformative potential. The purpose of this review is to define and assess the treatment strategy of “episensitization”, or the ability to sensitize cancer cells to subsequent therapy by resetting the epigenetic infrastructure of the tumor. One important facet is resensitization by epigenetic mechanisms, which goes against the norm, i.e., challenges the long-held doctrine in oncology that the reuse of previously tried and failed therapies is a clinically pointless endeavor. Thus, episensitization is a hybrid term, which covers recent clinically relevant observations and refers to the epigenomic mechanism of resensitization. Among the many formidable challenges in the treatment of cancer, the most inevitable is the development of acquired therapeutic resistance. Here, we present the basic principles behind episensitization and highlight the evidence suggesting that epigenetically mediated histone hypoacetylation and DNA hypermethylation events may reverse clinical drug resistance. The potential reversibility of epigenetic changes and the microenvironmental impact of epigenetic control on gene expression may mediate a return to a baseline state of treatment susceptibility. Episensitization is a novel and highly practical management strategy both to prevent the practice of permanent treatment discontinuation with the occurrence of resistance, which rapidly exhausts remaining options in the pharmaceutical armamentarium and to significantly extend patient survival. Accordingly, this review highlights several epigenetic agents including decitabine, vorinostat, entinostat, 5-azacitidine, oncolytic viruses and RRx-001.